2020
DOI: 10.7150/jca.42393
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Genotyping of Cryptosporidium parvum in Gastrointestinal Cancer Patients

Abstract: Gastrointestinal cancers are the most commonly occurring malignancies which contributing to over 1/5 of cancer incidences worldwide. Increasing evidences have shown that Cryptosporidium spp., an apicomplexan protozoan, is highly associated with gastrointestinal cancers. However, the prevalence of Cryptosporidium spp. infections among gastrointestinal cancer patients in China has not been estimated yet. We here performed a case-control study to evaluate the occurrences of Cryptosporidium spp. in patients with d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 36 publications
1
32
1
Order By: Relevance
“…We observed that STAg treatment significantly reduced oocyst shedding compared with the PBS treated group (p=0.030), indicating that STAg has a therapeutic or immunomodulatory effect against C. parvum infection (Fig 1A). The experiment was repeated with IFNγ-deleted mice infected with 1x10 5 Nano luciferase (Nluc) C. parvum oocysts Iowa II strain and oocyst shedding over time was quantified by NLuc expression (42). STAg treatment again significantly reduced the oocyst shedding (Fig 1B ; p=0.034) confirming our first results (Fig 1A).…”
Section: Stag Treatment Reduces the Oocyst Shedding In C Parvum Infected Ifnγ-deleted Micesupporting
confidence: 80%
See 2 more Smart Citations
“…We observed that STAg treatment significantly reduced oocyst shedding compared with the PBS treated group (p=0.030), indicating that STAg has a therapeutic or immunomodulatory effect against C. parvum infection (Fig 1A). The experiment was repeated with IFNγ-deleted mice infected with 1x10 5 Nano luciferase (Nluc) C. parvum oocysts Iowa II strain and oocyst shedding over time was quantified by NLuc expression (42). STAg treatment again significantly reduced the oocyst shedding (Fig 1B ; p=0.034) confirming our first results (Fig 1A).…”
Section: Stag Treatment Reduces the Oocyst Shedding In C Parvum Infected Ifnγ-deleted Micesupporting
confidence: 80%
“…In the ileum of infected-STAg treated mice, as compared to the uninfected-STAg treated mice, DEGs were associated with the mitochondrion (GO: 0005739), the extracellular region (GO:0005576), and the endoplasmic reticulum (GO:0005783) (Fig S3). Cellular component GO-terms had the highest level of enrichment for the cecum samples from STAg treated animals, which was not observed in biological process or molecular function GO terms (Fig S4 andFig5). Due to the localization of the parasite on the periphery of the host cell, it is encouraging that we observe GO terms that are related to the extracellular space and cellular trafficking when comparing infection status.…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…The other notable findings observed were the plausible associations of subtypes IIaA15G2R1 and IIaA15G2R2 in patients with colorectal cancer and IIaA13G2R2 subtype with both colorectal and liver cancers. 77…”
Section: Cryptosporidiosis In Cancer Patientsmentioning
confidence: 99%
“…where ⨂ denotes time domain convolution, , ( ) and , ( ) denote the impulse response of the I and Q SRRC filters of the i th subcarrier, respectively, which are given by [32]:…”
Section: System Setupmentioning
confidence: 99%